Pharmacy practice in Egypt - Elsayed, Tarek Mohamed Ali; Elsisi, Gihan H.; Elmahdawy, Mahmoud (Academic Press, Elsevier Inc., 2016)
Egypt is a historical country with a strategic location between Africa, Asia, and Europe. The practice of medicine and compounding was started thousands of years ago during the Pharaonic civilization. Egypt is one of the pioneers in the region with respect to modern pharmacy education and practice, which was started in the nineteenth century. Success has been achieved on many fronts in pharmacy practice in Egypt since the early 1990s. A large vaccine and generic medicine industry has been established. The number of pharmaceutical companies in Egypt is the largest in the region and production covers most of the local consumption. Some of the products are being exported to African, Middle Eastern, and Eastern European countries. A drug price control policy, which ensures affordable medicine prices, is being adopted. The number of pharmacy graduates in Egypt is the largest in the region, with many of them working in neighboring countries. Yet, many challenges face the pharmaceutical sector in Egypt. Inclusion of clinical pharmacy in pharmacy education and in hospital practice is essential. Also, the pharmaceutical industry needs to expand into the area of active pharmaceutical ingredients manufacturing.